2023
DOI: 10.1039/d2fd00164k
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of TiN catalysts during mechanocatalytic ammonia synthesis

Abstract: Mechanocatalytic ammonia synthesis is a novel approach toward ammonia synthesis under mild conditions. However, many open questions remain about the various mechanism of mechanocatalytic ammonia synthesis as well as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…X‐ray powder diffraction (XRD) has confirmed that the longer milled titanium becomes TiN. During the nitridation of titanium, the impact of the balls induces the formation of an amorphous structure and alters the surface morphology and porosity of the catalyst [36] . It is because the formation energy of TiN is low compared to other transition metal nitrides [37] .…”
Section: Ammonia Synthesis Via Mechanochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray powder diffraction (XRD) has confirmed that the longer milled titanium becomes TiN. During the nitridation of titanium, the impact of the balls induces the formation of an amorphous structure and alters the surface morphology and porosity of the catalyst [36] . It is because the formation energy of TiN is low compared to other transition metal nitrides [37] .…”
Section: Ammonia Synthesis Via Mechanochemistrymentioning
confidence: 99%
“…During the nitridation of titanium, the impact of the balls induces the formation of an amorphous structure and alters the surface morphology and porosity of the catalyst. [36] It is because the formation energy of TiN is low compared to other transition metal nitrides. [37] Therefore, nitrogen easily binds to the surface of titanium.…”
Section: Ammonia Synthesis With a New Approachmentioning
confidence: 99%
“…30 The surface chemistry and unique electronic structure of TiN make it an intriguing material for catalytic reactions, including ammonia synthesis, nitrogen fixation, and oxygen reduction. [31][32][33] Its potential as a replacement for expensive metal catalysts has sparked interest in developing TiN-based catalysts for sustainable and costeffective industrial processes. 34 The synthesis of TMNs can be achieved through a variety of methods, including chemical vapor deposition, reactive sputtering, and arc melting.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gas-phase ball mill reactions have been well documented in the literature and provide the key advantage of strong solid-gas interactions under ambient pressures and minimal solvent loads. [23][24][25][26] Furthermore, under ambient pressure gas flow conditions, the dangers of elemental hydrogen gas can be safely mitigated.…”
Section: Introductionmentioning
confidence: 99%